Development Of UNO Card Learning Media For Class XI Physics Learning - Gulo, Septa Harapan Jaya; Sitorus, Parlindungan; Sitinjak, Erni Kusrini; Marbun, Juliaster; Nainggolan, Juliper (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to develop a physics learning media in the form of UNO Cards to enhance students’ learning motivation in physics learning, particularly on the topic of heat for Grade XI high school students. The research employed the Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of five students in the small group trial and 19 Grade XI students from SMA Swasta Methodist 7 Medan in the field trial. The developed learning media was validated by content and media experts and was declared highly feasible, with an average feasibility score of 90% by content experts and 90.5% by media experts. The small group trial achieved an average feasibility score of 94%, while the field trial showed an average of 91%. In addition, the use of UNO Physics Cards was proven to increase students' learning motivation from the “moderate” category (65.18%) to the “very high” category (89%). The results indicate that the UNO Physics Card media is effective, feasible, and capable of increasing students’ motivation in learning physics. Therefore, this media can serve as an innovative alternative in classroom learning processes